Scrub typhus : A literature review - Arun Baranwal; S Vignesh Subramani (Wolters Kluwer Medknow Publications, 2019)
Scrub typhus is a mite-borne acute febrile illness caused by Orientia tsutsugamushi. Recently a surge in pediatric cases is noted across the country. This review focuses on the pathogenesis, clinical profile, diagnosis, management and critical care needs in children with scrub typhus.